Two new species and new records of Stilicoderus Sharp from China (Coleoptera, Staphylinidae, Paederinae) - Yu, Ting-Ting; Hu, Jia-Yao; Pan, Zhao-Hui (Zootaxa, 2016)
Two new species of the genus Stilicoderus Sharp, 1889 from China are described and illustrated: S. maolini sp. nov. (Jiangxi, Hunan) of the S. variolosus group and S. chengrani sp. nov. (Xizang) of the S. signatus group. Additional records of eleven described species of Stilicoderus are given.